Identification of the conditions required within an organisation for a talent management strategy to successfully be put in place - Tomany, A (Cranfield University, 2016)
Talent management has been viewed both as a relatively new phenomenon that can deliver competitive advantage and as the latest management fad that is nothing more than a sub-section of human resources. Much has been written on the subject, albeit predominantly by consultants, so there is little academic rigour on the subject. Moreover, the majority of the literature focused on highlighting the diminishing supply of talent and providing advice to practitioners around recruiting, retaining, developing and rewarding talent. This thesis reviewed the existing literature to provide a holistic view on talent management in order to add value both at the academic and practitioner level. It focussed on what conditions an organisation is advised to put in place in order to leverage the performance of talent and whether talent can have a significant impact on organisational performance. The secondary research suggested that talent could act as a lever for organisational performance. This was tested through primary research, from the organisational and individual perspective, and resulted in the identification of four conditions that impacted on the performance of talent. These conditions were grouped into a model, which was tested both by the case study organisations and by organisations that had not been involved in the research. The findings were used to adapt the model and this is offered for subsequent researchers to further develop in order to explore generalisability for all organisations.
Keywords: Personnel management; Management theory; Talent management